Preventing and managing workplace violence against healthcare workers in Emergency Departments. - d'Ettorre, Gabriele; Pellicani, Vincenza; Mazzotta, Mauro; Vullo, Annamaria (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: Healthcare workers (HCWs) employed in Emergency Departments (EDs) frequently face with patients becoming violent because of long wait or diseases or under the influence of alcohol or drugs. Globally, workplace violence (WPV) in EDs is a major challenge to safety for HCWs, involving significant consequences to the victims, patients, and healthcare organizations. We reviewed the current literature with the aim to explore the topics focused on and to detect new evidences about approaching the issue of WPV toward HCWs in EDs. Methods: A search for articles regarding WPV toward HCWs employed in EDs and published from January 2007 through December 2017 was performed; using predetermined criteria for inclusion, selected articles were reviewed and qualitatively assessed for the aims of the review. Results: We found 60 papers which matched our inclusion criteria; the topics, discussed in order of frequency from highest to lowest, were: “Risk Assessment”, “Occurrence Rates”, “Risk Management”, and “Physical/non Physical Consequences”. Dementia, schizophrenia, anxiety, acute stress reaction, suicidal ideation, and alcohol and drug intoxication were found as predictors of physical violence perpetrated by patients against HCWs. Conclusion: A strategic way to the effective management of WPV should prioritize training courses focused on: constructing HCW-patient relationship, improving the workers’ communication skills, accurate reporting of each violent incident, and improving the labor context through management commitment and employee involvement in WPV prevention programs. A special effort is required in implementing workplace design effective in minimizing stressful conditions in waiting rooms which turned out to be the most frequent site of assaults.